Esketamine mitigates endotoxin-induced acute lung injury by suppressing caspase-11-driven pyroptosis - Yunfei Bao; Zhihao Feng; Yanyan Niu; Qing Hu; Haijie Liu; Hongbo Zhang; Jianling Li (BMC Anesthesiology)
Abstract Background Acute lung injury (ALI) is a common complication of endotoxemia, which carries a high risk of morbidity and mortality. Currently, no effective drugs exist to treat endotoxin-induced ALI. This study evaluated esketamine’s protective effects against endotoxin-induced ALI and explored its underlying mechanisms. Methods Cecal ligation and puncture (CLP) was used to create a rat model of endotoxin-induced ALI. Esketamine (10 mg/kg) was injected into the tail vein of rats for drug treatment. The murine sepsis score (MSS) was used to evaluate the state of rats. Hematoxylin and eosin (HE) staining was used to evaluate lung tissue morphology and calculate the lung injury scores. The degree of lung tissue edema was assessed using the wet-to-dry weight (W/D) ratio. The expressions of caspase-11 and gasdermin D (GSDMD)-N, linked to the atypital pyroptosis pathway, were examined using immunohistochemistry (IHC) and western blot (WB) analysis. Caspase-11 and GSDMD mRNA levels were determined using quantitative real-time polymerase chain reaction (qRT-PCR). The expression of PI3K/AKT pathway was assessd using western blotting analysis. Interleukin (IL)-1β levels were quantified via enzyme-linked immunosorbent assay (ELISA). Results Esketamine treatment improved lung tissue structure, reduced pulmonary edema, and mitigated the inflammatory response in ALI. Esketamine inhibited caspase-11 and GSDMD expressions and decreased IL-1β levels, while reversing the inhibition of the PI3K/AKT pathway in ALI. Conclusion Esketamine mitigates CLP-induced ALI by suppressing the caspase-11-GSDMD pathway and reducing inflammation. The PI3K/AKT pathway may be involved in these protective effects.